Vessel wall imaging of vertebrobasilar artery configurations associated with posterior circulation infarction and high-risk atherosclerotic plaques - Jingtong Xiong; Yue Liu; Lingjun Mei; Chen Zhang; Jiying Xia; Honghai Chen; Xiaofeng Qu; Jianlin Wu (Scientific Reports)
Abstract The geometric configuration of the vertebrobasilar artery (VBA) can influence hemodynamic changes in the posterior circulation. This study aims to analyze the correlation of vascular morphology with posterior circulation infarction (PCI) and high-risk plaques on vessel wall imaging (VWI). A total of 249 atherosclerotic inpatients with 530 plaque segments located in the basilar artery (BA) and vertebral artery (VA) were retrospectively enrolled, comprising 98 PCI and 151 non-PCI patients. The configurations of VBA were classified on VWI and 3-dimensional time-of-flight magnetic resonance angiography (3D TOF-MRA), with a further quantitative evaluation conducted on VWI. VWI achieved higher diagnostic accuracy in detecting tuning fork, walking, and lambda VBA configurations, and revealed increased sensitivity in diagnosing VA hypoplasia (VAH), compared to TOF-MRA. Higher proportions of PCI and high-risk plaques were observed in the lambda and walking configurations than the tuning fork. No statistical difference in VAH was observed between the PCI and non-PCI groups (P = .972). Multivariable logistic regression analysis revealed that high-risk plaque [odds ratio (OR) = 1.997 (1.039–3.837), P = .038], the mean diameter of bi-VAs [OR = 1.557(1.012–2.395), P = .044], and the grade of BA lateral position [OR = 1.416 (1.029–1.950), P = .033] were independent risk factors associated with PCI. High-risk plaque segments featured larger vascular diameter, wall area, normalized wall index (NWI), remodeling index (RI), plaque volume, BA-midline, and vessel length compared with those with low-risk plaques (all P < .05). VWI offers the dual advantages of observing vascular morphology and evaluating high-risk plaques, which aids in the timely identification of individuals with PCI risks.